2021
DOI: 10.3390/atmos12091147
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Formation within Strong Northeasterly Environments in the South China Sea

Abstract: In the South China Sea (SCS), 17% of tropical cyclones (TCs) formed in the late season (November−January) were associated with a strong northeasterly monsoon. This study explores the effects of northeasterly strength on TC formation over the SCS. The Weather Research and Forecasting (WRF) model is used to simulate the disturbances that develop into TCs (formation cases) and those that do not (non-formation cases). Two formation (29W on 18 November 2001 and Vamei on 26 December 2001) and two non-formation (30 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…As a whole, the interdecadal variation of TC frequency in the SCS is linked to the phase transitions of the PDO. TC formation and development in the SCS in response to climate change highlights the role of dynamic factors (Lin et al., 2021; Sun et al., 2019). When PDO is in the negative phase, the more negative ZSG could modulate the atmospheric circulations at interannual and interdecadal time scales (Li & Zhou, 2014), which induces the eastward movement of the WPSH (Li et al., 2019; Figures 8d and 8e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a whole, the interdecadal variation of TC frequency in the SCS is linked to the phase transitions of the PDO. TC formation and development in the SCS in response to climate change highlights the role of dynamic factors (Lin et al., 2021; Sun et al., 2019). When PDO is in the negative phase, the more negative ZSG could modulate the atmospheric circulations at interannual and interdecadal time scales (Li & Zhou, 2014), which induces the eastward movement of the WPSH (Li et al., 2019; Figures 8d and 8e).…”
Section: Resultsmentioning
confidence: 99%
“…The SCS, a large semi‐enclosed marginal sea in the WNP (Figure 1a), is influenced by the climatic scale systems such as the East Asian monsoon and ENSO (Haghroosta & Ismail, 2017; Lin et al., 2021; Yan et al., 2011). The summer and winter SST in the northern SCS are influenced by the Western Pacific Warm Pool and the East Asian winter monsoon, respectively (Chen et al., 2018; Yan et al., 2015), while summer rainfall is affected by the East Asian summer monsoon (Ding & Chan, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, TCs over the SCS may have a closer connection with TCs over the BOB after summer. It was suggested that SCS TCs are even more active than those over the western North Pacific (WNP) during the late-season [14][15][16] . Although TC activity in the SCS peaks in the summer months, late-season TCs can still account for 31% of the annual TC frequency in this region (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, similar to the BOB, the SCS is also surrounded by land. The geography of bay and sea leads to a short warning period for countries surrounding the bay and the sea 16 , requiring deeper understanding of TC variability there.…”
Section: Introductionmentioning
confidence: 99%